1995
DOI: 10.1093/oxfordjournals.aje.a117386
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Intentional Weight Loss and Mortality in Never-Smoking Overweight US White Women Aged 40–64 Years

Abstract: Although 40% of US women indicate they are currently trying to lose weight, the association between intentional weight loss and longevity is unknown. The authors analyzed prospective data from 43,457 overweight, never-smoking US white women aged 40-64 years who in 1959-1960 completed a questionnaire that included questions on weight change direction, amount, time interval, and intentionality. Vital status was determined in 1972. Proportional hazards regression was used to estimate mortality rate ratios for wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
275
3
14

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(297 citation statements)
references
References 20 publications
5
275
3
14
Order By: Relevance
“…94,95 The impact of weight loss on cardiovascular risk factors is greatest in subjects with impaired glucose tolerance, type 2 diabetes, or hypertension, because changes in risk factors are more likely in subjects with abnormal baseline levels, and this is consistent with findings from observational studies that intentional weight loss is associated with increased longevity but only in people with pre-existing disease. 96,97 We found, however, that these improvements may be intervention specific. Orlistat therapy was associated with a 5-10% decrease in LDL levels, which is comparable to a cholesterol-lowering diet.…”
Section: Discussionmentioning
confidence: 63%
“…94,95 The impact of weight loss on cardiovascular risk factors is greatest in subjects with impaired glucose tolerance, type 2 diabetes, or hypertension, because changes in risk factors are more likely in subjects with abnormal baseline levels, and this is consistent with findings from observational studies that intentional weight loss is associated with increased longevity but only in people with pre-existing disease. 96,97 We found, however, that these improvements may be intervention specific. Orlistat therapy was associated with a 5-10% decrease in LDL levels, which is comparable to a cholesterol-lowering diet.…”
Section: Discussionmentioning
confidence: 63%
“…In one large American observational cohort study, women with BMI around 30 kgam 2 had a relative risk (RR) of CHD death that was only 20% lower than that of women with BMI of around 35 kgam 2 (Manson et al, 1995). Another epidemiological study suggested that an intentional weight loss of 9.1 kg was associated with a 25% reduction in cardiovascular mortality (Williamson et al, 1995). The true CHD risk reduction caused by the average 13.6 kg weight loss of our volunteers might lie somewhere between 20 and 50%.…”
Section: Discussionmentioning
confidence: 72%
“…Technical Review ± Nutritional management of diabetes mellitus TKK Ha and MEJ Lean Williamson et al, 1995). Longitudinal and actuarial evidence from diabetic individuals is not available to indicate an acceptable weight range different from the general population.…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%